ICT-Based Mathematics Learning Assessment: A Systematic Review of Effectiveness, Challenges, and Pedagogical Impacts - Syarif Hidayatullah; Elly Arliani; Kana Hidayati (Universitas Pendidikan Mandalika, 2025)
The importance of integrating Information and Communication Technology (ICT) into mathematics learning lies in its potential to enhance students’ critical thinking, problem-solving, and logical reasoning skills. Conventional assessments often face limitations in providing personalized and dynamic feedback. This study aims to examine the effectiveness, challenges, and pedagogical impacts of ICT-based mathematics assessment through a systematic review of literature published between 2020 and 2025. The research method employed is a Systematic Literature Review (SLR) following the PRISMA guidelines. Data were collected from the Scopus, WoS, ERIC, and Google Scholar databases using relevant keywords. The selection process involved identification, screening, eligibility assessment, and inclusion, resulting in n=15 articles for comprehensive analysis. The findings indicate that ICT-based assessment is effective in measuring cognitive domains, particularly conceptual understanding (33.3%), problem solving (26.7%), and learning outcomes (26.7%), while other aspects remain limited mathematical reasoning and self-assessment (13.3%). Furthermore, challenges in implementing ICT-based mathematics assessment include the design and development of instruments, technical and infrastructural limitations, teachers’ readiness and competencies, as well as student characteristics and the context of online learning. ICT-based assessment in mathematics also provides five main pedagogical impacts: enhancing student engagement and motivation, offering feedback and self-reflection, fostering cognitive and problem-solving skills, improving learning efficiency, and promoting pedagogical innovation.